Eluosi wa wa de mi mi - Cheng, Wei 1957- (Cai wu ya zhong wen yuan chuang xi lie, 2013)
Two German girls, neighbours, classmates and best friends, each have their own troubles. Charlotte's role-model father often spends his weekend alone somewhere and Maja's father disappears all of a sudden. When the two girls are lost in confusion, a neighbour sends them a mysterious Russian doll. As they open it layer by layer, a secret is revealed to them.